Protection of rat skeletal muscle fibers by either L-carnitine or coenzyme Q10 against statins toxicity mediated by mitochondrial reactive oxygen generation - La Guardia, Paolo G.; Alberici, Luciane C.; Ravagnani, Felipe G.; Catharino, Rodrigo R.; Vercesi, Anibal E. (Frontiers in Physiology, 2013)
Mitochondrial redox imbalance has been implicated in mechanisms of aging, various degenerative diseases and drug-induced toxicity. Statins are safe and well-tolerated therapeutic drugs that occasionally induce myotoxicity such as myopathy and rhabdomyolysis. Previous studies indicate that myotoxicity caused by statins may be linked to impairment of mitochondrial functions. Here, we report that one-hour incubation of permeabilized rat soleus muscle fiber biopsies with increasing concentrations of simvastatin (1-40 µM) slowed the rates of ADP-or FCCP-stimulated respiration supported by glutamate/malate in a dose-dependent manner, but caused no changes in resting respiration rates. Simvastatin (1 µM) also inhibited the ADP-stimulated mitochondrial respiration supported by succinate by 24% but not by TMPD/ascorbate. Compatible with inhibition of respiration, 1 µM simvastatin stimulated lactate release from soleus muscle samples by 26%. Co-incubation of muscle samples with 1mM L-carnitine, 100 µM mevalonate or 10 µM coenzyme Q10 (Co-Q10) abolished simvastatin effects on both mitochondrial glutamate/malate-supported respiration and lactate release. Simvastatin (1µM) also caused a 2-fold increase in the rate of hydrogen peroxide generation and a decrease in Co-Q10 content by 44%. Mevalonate, Co-Q10 or L-carnitine protected against stimulation of hydrogen peroxide generation but only mevalonate prevented the decrease in Co-Q10 content. Thus, independently of Co-Q10 levels, L-carnitine prevented the toxic effects of simvastatin. This suggests that mitochondrial respiratory dysfunction induced by simvastatin, is associated with increased generation of superoxide, at the levels of complexes-I and II of the respiratory chain. In all cases the damage to these complexes, presumably at the level of 4Fe-4S clusters, is prevented by L-carnitine.